Sexual dimorphism in relationships between of plasma uric acid and some psycho-neuro-endocrine parameters - Bombushkar, Igor; Korda, Mykhaylo; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. Earlier we found that effects of plasma nitrogenous metabolites as urea, creatinine, and bilirubin on neuro-endocrine parameters, as well as anxiety, are significantly different in men and women of different ages. The purpose of this study is to analyze the relationships between the plasma uric acid level and some psycho-neuro-endocrine parameters in the same cohort. Materials and Methods. The object of observation were almost healthy volunteers: 31 males (24÷69 y) and 30 females, from among them 18 postmenopausal (48÷76 y) and 12 of reproductive age (30÷45 y). In basal conditions we determined plasma levels of uric acid and adaptation hormones, estimated the severity of the trait and reactive anxiety, recorded the ongoing HRV and EEG. After 4 or 7 days, repeated testing was performed. Results. By uric acid regression models with stepwise exclusion, it was found that in men plasma uric acid downregulates the PSD of β-rhythm in P4 and δ-rhythm in others 4 loci, but upregulates the Asymmetry of δ-rhythm, variability of α-rhythm, PSD of θ-rhythm in P3 and O1 loci, Entropy of EEG in T4 as well as Testosterone plasma level. The measure of determination is 54,5%. In postmenopausal women, uricemia downregulates the Amplitude of β-rhythm and its PSD in 8 loci as well as sympathetic tone, but upregulates the PSD of HF and VLF bands HRV, Testosterone plasma level, PSD of θ-rhythm in F3 and O2 loci as well as the Laterality of δ-rhythm. The degree of determination of neuro-endocrine parameters is 94,4%. In women of reproductive age uricemia upregulates the Asymmetry and Amplitude of β-rhythm and its PSD in 6 loci, the Amplitude and Laterality of θ-rhythm and its PSD in F8 locus, as well as the PSD of α-rhythm in F8 locus. The degree of positive determination of EEGs parameters is 95,5%. Conclusion. Plasma uric acid has a modulating effect on neuro-endocrine parameters, but this effect is significantly different in men and women of different ages, which is due, apparently, to the influence of sex hormones on the expression of adenosine receptors in neurons.